Early cystic fibrosis lung disease: Role of airway surface dehydration and lessons from preventive rehydration therapies in mice - Mall, Marcus A.; Gräber, Simon Y.; Stahl, Mirjam; Zhou-Suckow, Zhe (International journal of biochemistry & cell biology, 2014)
Cystic fibrosis (CF) lung disease starts in the first months of life and remains one of the most common fatal hereditary diseases. Early therapeutic interventions may provide an opportunity to prevent irreversible lung damage and improve outcome. Airway surface dehydration is a key disease mechanism in CF, however, its role in the in vivo pathogenesis and as therapeutic target in early lung disease remains poorly understood. Mice with airway-specific overexpression of the epithelial Na+ channel (βENaC-Tg) recapitulate airway surface dehydration and phenocopy CF lung disease. Recent studies in neonatal βENaC-Tg mice demonstrated that airway surface dehydration produces early mucus plugging in the absence of mucus hypersecretion, which triggers airway inflammation, promotes bacterial infection and causes early mortality. Preventive rehydration therapy with hypertonic saline or amiloride effectively reduced mucus plugging and mortality in neonatal βENaC-Tg mice. These results support clinical testing of preventive/early rehydration strategies in infants and young children with CF.